PERSONALITY TRAITS AND DECISION- MAKING STYLES IN GET-RICH-QUICK SCHEME INVESTMENTS - Mazlan, Ahmad Rizal; Salim, Azlizamani Zubir; Othman, Fazilah; Bakar, Md Zawawi Abu (CENTRAL ASIA AND THE CAUCASUS, 2024)
Various types of investment schemes, both legal and illegal, are available to investors globally, including in Malaysia. The legal investments are quite clear as they are offered by financial institutions and the transactions usually occur in established capital markets. The illegal investment schemes, on the other hand, can be quite difficult to identify. Among them are the get-rich-quick schemes or infamously known as Ponzi schemes, which have adversely affected many individuals for the past few decades. This article focuses on how personality traits affect decision- making among investors, particularly in get-rich-quick schemes. By examining the relevant literature, this concept paper shows that personality traits significantly influence investment decisions, including the get-rich-quick schemes. Specifically, five elements have beenidentified as the contributing factors, namely, i) behavioral bias ii) emotional bias iii) cognitive bias, iv) overconfident personality and v) lack of shariah compliant. These factors need to be given attention by the government in addressing the issue of illegal get-rich-quick schemes. Furthermore, the study also suggests that the authorities need to develop investor personality profiler and guidelines to invest in legal and Sharia- compliant investments.